Uterine Didelphys Associated With Obstructed Hemivagina and Ipsilateral Renal Anomaly (OHVIRA) Syndrome: a Case Report - Parvin, A; Khan, BS; Alam, J; Ruby, FA; Iqbal, TJ (Pulse, 2014)
A 30 year old nulligravida female reported to the fertility centre of AHD with the complaints of primary infertility for three and half years and spasmodic dysmenorrhoea. There is also history of progressively increasing right lower abdominal pain as well as discomfort which was cyclically associated with the onset of menses. Transabdominal sonography showed-Endometrial splitting into two at the fundussuggesting bicornuate uterus. Echogenic soft tissue in the cervical canal due to blood clots. Non visualized right kidney. Mildly enlarged left kidney. HSG done outside AHD suggestive of unicornuate uterus with single fallopian tube. IVU showed non visualized right kidney. Normally excreting left kidney. TVS showed normal sized septated nulliparus uterus with homogeneous myometrium and thick endometrium with proliferative phase echo. Mildly enlarged right ovary with mildly distended right tube. Mild collection adjacent to the vagina. Then the patient came to the gynaecology dept of AHD from where she was sent to our Radiology department to undergo MRI of pelvis. The MRI showed uterine didelphys. Obstructed hemivagina (right) with hematocolpos extended upto pelvic brim along right and posterior aspect of uterus through anomalous dilated remnant of right lower ureter with ipsilateral renal agenesis. Patient was diagnosed as OHVIRA syndrome radiologically. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20358 Pulse Vol.6 January-December 2013 p.66-69